2022
DOI: 10.7150/ijbs.70620
|View full text |Cite
|
Sign up to set email alerts
|

GPR125 positively regulates osteoclastogenesis potentially through AKT-NF-κB and MAPK signaling pathways

Abstract: G-protein-coupled receptors (GPCRs) signaling is critical to cell differentiation and activation. However, the function of GPCRs in osteoclast differentiation and activation remains unclear. We found that the G-protein coupled receptor 125 (GPCR 125) gene (Gpr125) gene was highly expressed in osteoclasts through RNA-sequencing technology, qRT-PCR, and Western blot analysis. We characterized the role of GPCR125 in osteoclast differentiation and activation by loss-of-function and gain-of-function methods in oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Nevertheless, ADGRA3 deficiency was associated with a significant reduction in established hallmarks of long-term estrogen signaling, such as femoral BMD, consistent with previous studies [ 40 ]. However, as ADGRA3 was recently described as a positive regulator of osteoclastogenesis [ 57 ], and normal osteoclast activity is needed for dynamic bone remodeling, it is possible that the impaired BMD was also affected directly by the low ADGRA3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, ADGRA3 deficiency was associated with a significant reduction in established hallmarks of long-term estrogen signaling, such as femoral BMD, consistent with previous studies [ 40 ]. However, as ADGRA3 was recently described as a positive regulator of osteoclastogenesis [ 57 ], and normal osteoclast activity is needed for dynamic bone remodeling, it is possible that the impaired BMD was also affected directly by the low ADGRA3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…PTEN has been identified as an important regulator in RANKL‐induced osteoclastogenesis and participates in the regulation of the phosphorylated inositol 3‐kinase (PI3K)/AKT pathway through the dephosphorylation of phosphatidylinositol 3,4,5‐triphosphate (PIP3) 131,132 . AKT directly phosphorylates and activates IKKs to promote IκB degradation, thereby activating the NF‐κB pathway 133 . Huang et al 28 found that USP13 directly interacted with PTEN and inhibited its ubiquitination‐related degradation.…”
Section: Effects Of Usps On Osteoclastogenesis and Bone Resorptionmentioning
confidence: 99%
“…In addition, overexpression of USP13 also increased serum OPG levels, decreased RANKL levels in synovial tissues, and attenuated bone destruction in mice with collagen‐induced arthritis (CIA) 28 . Proinflammatory NF‐κB and PI3K/AKT signalling has also been shown to be among the most important contributors to induce particle‐induced inflammatory reactions in macrophages and bone cell lysis 133–135 . NOD‐like receptor family CARD domain‐containing 5 (NLRC5), a negative regulator that blocks IKKα and IKKβ activity, inhibits the activation of the PI3K/AKT and NF‐κB signalling pathways 136 .…”
Section: Effects Of Usps On Osteoclastogenesis and Bone Resorptionmentioning
confidence: 99%
“…Previous research has shown that M‐CSF promotes osteoclast proliferation and enhances the expression of receptor activators of nuclear kappa‐B (RANK) on the osteoclast cell membrane RANKL (Mun et al, 2020). Through its receptor RANK, RANKL encourages osteoclast differentiation by attracting TNF receptor‐associated factor 6 (Liu et al, 2021; Tang et al, 2022) and activating various downstream signaling pathways, including reactive oxygen species (ROS), nuclear factor‐kappa B (NF‐κB), and mitogen‐activated protein kinase (MAPK) (Bai et al, 2020; Holmström & Finkel, 2014; Sies & Jones, 2020). The expression of functional proteins corresponding to osteoclasts and nuclear factor activated T‐cells 1 (NFATc1) is strongly influenced by these pathways (Bae et al, 2023; Ibáñez et al, 2022).…”
Section: Introductionmentioning
confidence: 99%